CARACTERIZAÇÃO E HERDABILIDADE DE CARACTERES AGRONÔMICOS E DE QUALIDADE EM LINHAGENS DE AVEIA CONDUZIDO EM AUGUSTO PESTANA, RS - Arenhardt, Emilio G.; Gaviraghi, Juliano; Martins, Luis F. d. S.; Battisti, Gabriel K.; Bandeira, Taiane P.; Antonow, Diovane; Matter, Edegar; Maixner, Adriano R.; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo